Exploration of anionic inhibition of the α-carbonic anhydrase from Thiomicrospira crunogena XCL-2 gammaproteobacterium: A potential bio-catalytic agent for industrial CO2 removal. (22nd December 2015) - Mahon, Brian P.; Bhatt, Avni; Vullo, Daniela; Supuran, Claudiu T.; McKenna, Robert
Abstract: The α-class carbonic anhydrase (CA) from the thermophilic gammaproteobacterium Thiomicrospira crunogena XCL-2 (TcruCA) has been recently proposed as a candidate enzyme for carbon dioxide removal (CDR) in flue gas scrubbing systems. However during this process, the enzyme may be exposed to anionic impurities which can limit the use of CA for CDR. The inhibition of TcruCA by various anions, some of which are found in flue gas, is reported. The majority of the anions tested display weak (mM) inhibition but some, such as the metal poisons and anionic acids, exhibit stronger (μM) inhibition. Most relevant to the use of CA in CDR is the inhibition by SO x, NO x, and Hg 2+, which can be removed through a pre-scrubbing treatment. In addition, the active site structural architecture of TcruCA is compared with other α-class CAs and differences in catalytic efficiency and anion inhibition are discussed. This study provides information regarding anionic inhibition of CAs as bio-catalytic CDR agents and the results should therefore be considered in the design of CA-mediated flue gas scrubbing systems. Graphical abstract: Highlights: The α-CA from Thiomicrospira crunogena XCL-2 (TcruCA) is a candidate for CO2 removal. Anions found in flue gas (Hg 2+, SO4 2−, NO2 −, and NO3 − ) inhibit TcruCA in the mM range. Active site residue differences between CAs may explain the anion inhibition profiles.